Temperature-dependent structure evolution in liquid gallium. (15th April 2017) - Xiong, L.H.; Wang, X.D.; Yu, Q.; Zhang, H.; Zhang, F.; Sun, Y.; Cao, Q.P.; Xie, H.L.; Xiao, T.Q.; Zhang, D.X.; Wang, C.Z.; Ho, K.M.; et al.
Abstract: Temperature-dependent atomistic structure evolution of liquid gallium (Ga) has been investigated by using in situ high energy X-ray diffraction experiment and ab initio molecular dynamics simulation. Both experimental and theoretical results reveal the existence of a liquid structural change around 1000 K in liquid Ga. Below and above this temperature the liquid exhibits differences in activation energy for self-diffusion, temperature-dependent heat capacity, coordination numbers, density, viscosity, electric resistivity and thermoelectric power, which are reflected from structural changes of the bond-orientational order parameter Q 6, fraction of covalent dimers, averaged string length and local atomic packing. This finding will trigger more studies on the liquid-to-liquid crossover in metallic melts. Graphical abstract: Atomistic structure evolution of liquid gallium has been investigated by using in situ high energy X-ray diffraction and ab initio molecular dynamics simulations, which both demonstrate the existence of a liquid structural change together with reported density, viscosity, electric resistivity and absolute thermoelectric power data. Image